Phytochemical screening and antimicrobial activity of methanolic leaf extract of Securidaca longipedunculata Fresen (Polygalaceae) - Auwal Sani (Journal of Current Biomedical Research, 2023)
The present occurrence of drug resistance by most microorganisms has posed an enormous problem in the health care and triggered the need for continuous research for better and safe therapeutic agents. Securidaca longipedunculata is locally used in treating skin infections. Thus this study was designed to investigate the phytochemical constituents and antimicrobial activities of methanol leaf extract of Securidaca longipedunculata against Streptococcus pyogenes, Staphylococcus aureus and Candida albicans which are known to cause skin infections. Antimicrobial activity against the organisms was determined using agar well diffusion method. Four concentrations of the leaf extract were prepared and used in the study (800 mg/ml, 400 mg/ml, 200 mg/ml, and 100 mg/ml). Minimum Bactericidal Concentration (MBC) and Minimum Fungicidal Concentration (MFC) of the extract were also analysed. Upon extraction, the phytochemical constituents of the leaf were found to be carbohydrate, saponins, flavonoids, alkaloids, steroids, cardiac glycosides, tanins and anthraquinones. There was no activity observed at 200 and 100 mg/ml concentrations of the extract on all the test organisms. For the Minimum Inhibitory Concentration (MIC) test against all the tested bacterial isolates, the MIC was found to be 400 mg/ml. In the MBC test, the test showed that S. pyogenes and S. aureus were not killed by the leaf extract but rather they were inhibited from growing this is the same with C. albicans in the MFC. This study the use of the leaf of S. longipedunculata in traditional medicine for topical application in skin infections.